The lack of ethnically sensitive data in Serbia's multiculturalism policy - Bašić Goran; Lutovac Zoran (Stanovništvo)
International organisations whose bodies monitor the realisation and protection of the rights of national and ethnic minorities (Council of Europe, United Nations) have expressed their concern about the lack of data in the Republic of Serbia’s reports on the protection of the rights of national minorities, and they have provided some recommendations in order to amend the situation. Prompted by these remarks, this paper considers the flaws in Serbia’s policy of multiculturalism. The main finding – that Serbia’s policy of multiculturalism is not founded on verified and measurable data – has been examined further by indicating the principles and methodologies of collecting data based on ethnic and national identity. By using a range of examples, the paper points to the social issues that occur due to neglect in collecting data on citizens’ ethnicity, while the necessity of an interdisciplinary approach to collecting such data is also considered. A holistic approach to researching ethnicity assumes using not only demographic methods, but also methods from and knowledge of other social sciences and humanities. The United Nations supports the idea that the approach to ethnically sensitive data should be holistically founded with its position that all data regarding people’s identity must be based on human rights – a Human Rights-Based Approach to Data (HRBAD), in which case the relevance of statistical data is promoted.